PENGARUH TERAPI SENI TIE-DYE TERHADAP KEPUASAN HIDUP PASIEN SKIZOFRENIA DI RSJD Dr. RM. SOEDJARWADI KLATEN - Dzakiya , Evita Lubban; Untari, Rita (Medical Journal of Nusantara, 2024)
Schizophrenia is a psychosocial disorder that affects behavior, feelings, strange delusions, and chaotic thinking patterns. Schizophrenia patients experience a decrease in life satisfaction and well-being related to physical, social, and psychological conditions in carrying out daily activities. Art therapy has the potential to be a way to minimize existing negative symptoms and overcome life stress. This study aims to determine the effect of tie-dye art therapy on the life satisfaction of schizophrenia patients at RSJD Dr. RM. Soedjarwadi Klaten. Research method: Quantitative research using a one-group pre-test-post- test pre-experimental design. The sampling technique uses purposive sampling. The research sample was 21 schizophrenia patients. Life satisfaction was measured using the Satisfaction With Life Scale (SWLS) instrument. Hypothesis testing uses the paired sample t-test. Research results: The sample was dominated by those aged 17-25 years (33.3%), men (61.9%), junior high school education (71.4%), and unmarried (42.9%). After the sample received 6 sessions of tie-dye art therapy treatment/intervention, the sample experienced an increase in the mean SWLS score. The life satisfaction hypothesis test showed a p-value of 0.000 (<0.05). This means that there is an influence of tie-dye art therapy on the life satisfaction of schizophrenia patients at RSJD Dr. RM. Soedjarwadi Klaten. In batik therapy, patients can express expressions that cannot be expressed directly, increasing happiness and increasing life satisfaction for schizophrenic patients in RSJ who are undergoing rehabilitation. Conclusion: Tie-dye art therapy influences the life satisfaction of schizophrenia patients at RSJD Dr. RM. Soedjarwadi Klaten.